A Methodology to Predict the Substitutability of Robots for Factory Workers - AYRES, Robert U. (Institutional Knowledge at Singapore Management University, 1984)
A framework is proposed for measuring the difficulty of substituting a robot for semiskilled and unskilled workers in factories. Motivations for the framwork are given in the first paper. The Sensory Feedback Dependence of Assembly Tasks as a Measure of Comparative Advantage of Human Workers vis-a-vis Sensor-Based Robots; by R. U. Ayres. The basic premise is that the more a human's performance is degraded by interference with visual and tactile senses, the more difficult and expensive it would be to substitute a robot for a human. It is proposed that for types of tasks where there is a trade-off between performance time and precision, the relative degradation in human task performance due to sensory deprivation is a useful measure of the difficulty of replacing a worker with a robot. Results of experiments where the visual and tactile input to human subjects is degraded and the time to assemble different devicies is measured are reported in the second paper, Human Assembly Time versus Levels of Visual and Tactile Sensory Input; Experimental Results for Five Devices', by S. M. Miller. The results show that (1) there is an inverse relationship between the amount of visual and tactile sensory input and the time required to assemble a device, (2) that the relative degradation in assembly time due to sensory deprivation varies greatly across different assembly jobs, and (3) that assembly jobs which are extremely sensitive to the degradation of visual and/or tactile input can be identified. Estimates of the sensitivity of elemental and manipulative subtasks (e.g. reach, grasp, move position, turn) to degradations in visual and tactile input are also reported.